2009
DOI: 10.1007/s10517-009-0624-x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Afobazole with σ1-Receptors

Abstract: In vitro radioligand assay revealed interaction of afobazole with sigma(1)-receptors (Ki=5.9x10(-6) M). Translocation of sigma(1)-receptors from the endoplasmic reticulum to the outer membrane was demonstrated by confocal microscopy. Experiments were performed on the model of HT-22 immortalized hippocampal cells after incubation with afobazole in a concentration of 10(-8) M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 7 publications
(5 reference statements)
2
17
0
Order By: Relevance
“…Activation of receptors has been linked to inhibition of microglial cell migration and afobazole has been suggested to interact with receptors (Seredenin et al, 2009). Experiments were carried out to determine whether afobazole acts through receptors in microglial cells to inhibit migration.…”
Section: Resultsmentioning
confidence: 99%
“…Activation of receptors has been linked to inhibition of microglial cell migration and afobazole has been suggested to interact with receptors (Seredenin et al, 2009). Experiments were carried out to determine whether afobazole acts through receptors in microglial cells to inhibit migration.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is unclear whether afobazole is acting directly on caspase-3 or through some upstream signaling molecule. Another putative afobazole target for neuroprotection is receptors, which have been postulated as an effector for this drug (Seredenin et al, 2009). Afobazole has a pharmacophore structure similar to that of the -1-receptor agonist (ϩ)-pentazocine.…”
Section: Discussionmentioning
confidence: 99%
“…Afobazole has a pharmacophore structure similar to that of the -1-receptor agonist (ϩ)-pentazocine. Binding studies showed that afobazole displaces (ϩ)-pentazocine in Jurkat cells with an IC 50 of 7 M (Seredenin et al, 2009). Application of afobazole onto HT-22 cells results in translocation of -1 receptors from the cell body to axons, suggesting possible activation of the receptors by afobazole (Seredenin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations